2014
DOI: 10.1016/b978-0-12-800249-0.00001-9
|View full text |Cite
|
Sign up to set email alerts
|

Glial Progenitors as Targets for Transformation in Glioma

Abstract: Glioma is the most common primary malignant brain tumor and arises throughout the central nervous system (CNS). Recent focus on stem-like glioma cells has implicated neural stem cells (NSCs), a minor precursor population restricted to germinal zones, as a potential source of gliomas. In this review, we will focus on the relationship between oligodendrocyte progenitor cells (OPCs), the largest population of cycling glial progenitors in the postnatal brain, and gliomas. Recent studies suggest that OPCs can give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 322 publications
0
32
0
Order By: Relevance
“…Gliomas are tumours of the central nervous system (CNS), originating from transformed neural stem or progenitor glial cells [32]. The World Health Organisation (WHO), based on histopathological characteristics, divided gliomas into groups: low-grade gliomas (grades I and II) are benign, well-differentiated, slow-growing tumours; whereas high-grade gliomas (grades III and IV) are poorly differentiated or anaplastic, rapidly proliferating, and strongly infiltrate brain parenchyma.…”
Section: Accumulation and Functions Of Myeloid Cells In Gliomasmentioning
confidence: 99%
“…Gliomas are tumours of the central nervous system (CNS), originating from transformed neural stem or progenitor glial cells [32]. The World Health Organisation (WHO), based on histopathological characteristics, divided gliomas into groups: low-grade gliomas (grades I and II) are benign, well-differentiated, slow-growing tumours; whereas high-grade gliomas (grades III and IV) are poorly differentiated or anaplastic, rapidly proliferating, and strongly infiltrate brain parenchyma.…”
Section: Accumulation and Functions Of Myeloid Cells In Gliomasmentioning
confidence: 99%
“…Glioma is the most common malignant primary brain tumor which arises from the central nervous system [1]. The tumor is highly aggressive with a mean survival time of nine to twelve months from diagnosis to death.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cell cycling of CD133+ GBM cells is influenced by the tumor microenvironment (15), which also evolves in association with treatment. Recent studies have identified many alternative TPC markers in human GBM (16). The cell surface sialoglycoprotein podoplanin (PDPN) shows partial co-expression with CD133 in GBM cultures and tissues (15, 17).…”
Section: Introductionmentioning
confidence: 99%